PENERAPAN INTERNET OF THINGS (IOT) SEBAGAI SISTEM MONITORING PARAMETER OUTPUT GENSET 3 PHASE - Ihsan; Qory Hidayati; Nur Yanti, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
A generator set (genset) is an important piece of equipment to support a backup power supply when the main power source is interrupted. In the use of generators, it is necessary to carry out regular monitoring, to ensure that the electricity produced by the generator is not disturbed. This study aims to provide a solution in monitoring generator condition real-time. This system can monitoring output the generator consists of voltage (V), current (I), and power (W) through the Android application. This system uses the PZEM-004Tv30 sensor, and a DC voltage sensor connected to the ESP8266 as microcontroller to process the data read by the sensor. This system is feature packed history sensor readings using google spreadsheet and this system uses the warning indication feature using the application Telegram when the voltage of the generator and the battery under voltage and over voltage. The results showed the difference between the PZEM-004Tv30 sensor readings and output phase R that is, a voltage of 0.02 V and a current of 0.1 A, and utput phase S shows a voltage difference of 0.3 V and a current of 0.07A, and utput phase T shows a difference in voltage of 0.1 V, and a current of 0.04 A, the DC voltage sensor with the battery gets a difference in value of 0.02 V. The results of this study show that the system has a high degree of accuracy. The installation of this system is expected to assist in monitoring the condition of the generator and reduce the risk of unexpected damage.